Development of a low cost digital beamforming radar - Song, Renjian (2015)
Digital Beamforming is advance and important concept in Radar system evolution. Nowadays, digitalization rapidly increase the speed of technology with relatively convenience and low expense. Software define radio (SDR) advance technology on wireless communication system provide a low cost and fixable method to build up wireless system. It has been widely used in developing wireless communication project. This project deliver a way to construct a low cost Beamforming Radar using Software Define Radio (SDR). The project is divided into two part, Software define radar implementation and low cost Beam forming radar implementation. The radar chirp signal generation and received signal processing in match filter is conducted using MATLAB platform. The the Radar transceiver will be implemented through antenna and Universal Software Radio peripheral (USRP) controlled by USRP Hardware driver using C++. After that, the digital Beam forming radar is developed based on regular Software Define Radar in USRP and MATLAB system resulting with good resolution Beam forming. However, the limitation on performance depend on the quality and speed of computer.